SAT0243 The effect on toxicity of reducing the size of available paracetamol pack sizes in the united kingdom. (1st June 2001) - Sheen, CL; Dillon, JF; Bateman, DN; Simpson, K; MacDonald, TM
Abstract : Background: Analgesia, using such drugs as paracetamol, is vital in the treatment of arthritis. Unfortunately, the incidence of paracetamol overdose, a common cause of hepatotoxicity and death, has been increasing. In the United Kingdom as a means of reducing adverse event risk, the Medicines Control Agency (MCA) limited the pack size of over-the-counter paracetamol in September 1998. This reduction in the amount that can be purchased may make obtaining paracetamol more difficult for people with arthritis. Objectives: To determine paracetamol overdose rates for patients presenting to Ninewells Hospital, Dundee and to assess whether the action by the MCA has had any measurable effect. Methods: Using serum paracetamol levels as a robust marker for overdose, the biochemistry database was searched for all paracetamol assay requests for each 12-month period from September 1995 to September 2000. We recorded all requests, all assays with measurable paracetamol and results that were potentially hepatotoxic 4 h after ingestion (> 1.3 mmol/l). The numbers of presentations of paracetamol overdose were compared before and after September 1998. Results: A total of 6336 tests were performed of which 4454 (70.1%) were negative for paracetamol. The Table 1 shows the number of tests by year and result. Using the Chi Squared test there were no significant differences before and after September 1998 (p = 0.7). Conclusion: These results do not suggest that the incidence of paracetamol overdose has been affected by the over-the-counter pack size reduction at least in the Tayside region of Scotland. Further measures to reduce the burden of paracetamol overdose to the healthcare system must be considered along with effective ways of obtaining paracetamol for appropriate clinical use.